Gut microbiota in anxiety and depression: Pathogenesis and therapeutics - Bibbò, Stefano; Fusco, Salvatore; Ianiro, Gianluca; Settanni, Carlo Romano; Ferrarese, Daniele; Grassi, Claudio; Cammarota, Giovanni; Gasbarrini, Antonio (Frontiers in Gastroenterology, 2022)
Depression and anxiety disorders represent a burdensome clinical issue. Considering the unsatisfactory clinical response of some patients to antidepressant therapy, new personalized approaches are being studied. In recent years, pre-clinical and clinical studies have investigated the role of intestinal microbiota demonstrating the importance of the gut-brain axis in these diseases. Indeed, gut microbes are able to interact with the brain interfering with behavior through some mechanisms such as amino acid metabolism, short–chain fatty acids, vagus nerve, endocrine signaling and immune responses. Experiments of gut microbiota transfer from subjects with major depression to animal models corroborated the causative role of intestinal microbes in mood disorders and anxiety. Furthermore, the incidence of dysbiosis in patients with anxiety and depression suggests a potential role for gut microbiota modulators in the treatment of these disorders. In particular, several probiotics and synbiotics have been shown to be effective in improving clinical symptoms, promising results have emerged also from fecal microbiota transplantation, but the evidence is still limited. These promising results switch on the use of gut microbiota modulators as an adjunctive tool to anti-depressant therapy. Developing pharmaceutical or nutraceutical strategies to modify the composition of gut microbiota may offer novel and personalized therapeutic tools against anxiety and depression.